Effect of NPK Mestibiru Fertilizer and Mamigro Fertilizer on the Growth and Yield of Mustard (Brassica rapa L.), Chia Tai Variety - Hery Sutejo; Marisi Napitupulu; Wawan Setiawan; Abdul Fatah (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The objectives of the study were: to determine the effect of NPK Mestibiru fertilizer and Mamigro leaf fertilizer and their interaction on the yield of mustard greens; and to determine the proper dose of NPK Mestibiru fertilizer and Mamigro fertilizer concentration for mustard greens (Brassica rapa L), Chia Tai variety. The research was carried out for two months, starting from March 2021 to April 2021.  It was located in Melak village, Melak sub District, West Kutai Regency, East Kalimantan Province, Indonesia. The study used a factorial experiment in a completely randomized design (CRD) 3 x 3, with 4 replications.  Factor I was the dose of NPK Mestibiru fertilizer (B), consisting of 3 levels, namely: bo = no NPK Mestibiru fertilizer application or control; b1 = 200 kg/ha (5 g/polybag), and b2 = 400 kg/ha (10 g/polybag).  Factor II was the concentration of Mamigro fertilizer (M), consisting of 3 levels, namely: mo = no Mamigro fertilizer; m1 = 2 g/l.water, and m2 = 4 g/l.water.  Data analysis was counted by analysis of variance and continued with the BNT test at 5% level. The results indicated that: (1) Treatment of NPK Mestibiru fertilizer (B) had a significant to very significant effect on the plant height and number of leaves at aged 10, 20 and 30 days after planting, and fresh weight per plant;  (2) Mamigro (M) fertilizer treatment had a significant to very significant effect on the plant height and number of leaves at aged 10, 20, and 30 days after planting, and fresh weight per plant;  and (3) The interaction between NPK Mestibiru fertilizer and Mamigro fertilizer had no significant effect on the plant height and number of leaves at aged 10, 20, and 30 days after planting, but it had a very significant effect on the fresh weight per plant.  The highest plant fresh weight was produced in the combination of b2m2, which was 247.25 g, while the lowest one was produced in the treatment no NPK Mestibiru fertilizer and no Mamigro fertilizer (b0m0), which was only 98.50 g.